2010
DOI: 10.1007/s10532-010-9351-2
|View full text |Cite
|
Sign up to set email alerts
|

para-Nitrophenol 4-monooxygenase and hydroxyquinol 1,2-dioxygenase catalyze sequential transformation of 4-nitrocatechol in Pseudomonas sp. strain WBC-3

Abstract: Pseudomonas sp. strain WBC-3 utilizes para-nitrophenol (PNP) as a sole source of carbon, nitrogen and energy. PnpA (PNP 4-monooxygenase) and PnpB (para-benzoquinone reductase) were shown to be involved in the initial steps of PNP catabolism via hydroquinone. We demonstrated here that PnpA also catalyzed monooxygenation of 4-nitrocatechol (4-NC) to hydroxyquinol, probably via hydroxyquinone. It was the first time that a single-component PNP monooxygenase has been shown to catalyze this conversion. PnpG encoded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…While PnpA1 (80% identical to PnpA), PnpC, PnpD, PnpE, and PnpF exhibit high degrees of identity with the enzymes involved in PNP degradation from several PNP utilizers (3-6), PnpG has a high level of identity with the BT 1,2-dioxygenase of Pseudomonas sp. strain WBC-3 (37).…”
Section: Resultsmentioning
confidence: 99%
“…While PnpA1 (80% identical to PnpA), PnpC, PnpD, PnpE, and PnpF exhibit high degrees of identity with the enzymes involved in PNP degradation from several PNP utilizers (3-6), PnpG has a high level of identity with the BT 1,2-dioxygenase of Pseudomonas sp. strain WBC-3 (37).…”
Section: Resultsmentioning
confidence: 99%
“…strain A1 (Spain and Gibson 1991), Pseudomonas spp. (Liu et al 2005; Wei et al 2010) usually degrade PNP via formation of ‘hydroquinone’ (HQ) as the ring cleavage substrate. A few studies have indicated conversion of HQ into BT, which is then used as the terminal ring cleavage substrate in the degradation of 4-hydroxybenzoate and p -nitrophenol by Candida parapsilosis CBS604 and Pseudomonas aeruginosa HS-D38 respectively (Figure 1A) (Eppink et al 2000; Zheng et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine gentisate 1,2-dioxygenase activity, the formation of maleylpyruvate was measured at 330 nm (ε 330 = 10.800/M cm) (Feng et al, 1999). The activity of hydroxyquinol 1,2-dioxygenase was measured spectrophotometrically by the formation of maleyla cetate at 243 nm (ε 243 = 44.520/M cm) (Wei et al, 2010). One unit of enzyme activity was defined as the amount of enzyme required to generate 1 µmol of product per minute.…”
Section: Methodsmentioning
confidence: 99%